中国钻石零售市场分析及营销对策初探 = The market of retail diamonds and sales strategy in China - 谈宏伟 Tan, Hong Wei (2011)
In view of the rapid economic progress and the rise in living standards, diamond trade has become a lucrative business in China. The market of retail diamonds offers great potential for development and expansion. This dissertation commences with a macro review of the evolution and development of diamond industry in China. It then moves to identify the niche market for the product through an analysis of product attributes, marker demand, and the pace of market development in the country. Based on the foregoing analyses, this dissertation further discusses the relevant marketing strategies such as pricing, advertisements and promotion for the product. It also proposes that large conglomerate could participate in this growing market to reap the benefits on innovation and economy of scale. The dissertation ends with clear and concise conclusions and recommendations, which have implications for market practitioners of the diamond industry in China.